Distinct pattern of oculomotor impairment associated with acute sleep loss and circadian misalignment. (6th August 2019) - Stone, Leland S.; Tyson, Terence L.; Cravalho, Patrick F.; Feick, Nathan H.; Flynn‐Evans, Erin E.
Abstract : Key points: Inadequate sleep and irregular work schedules have not only adverse consequences for individual health and well‐being, but also enormous economic and safety implications for society as a whole. This study demonstrates that visual motion processing and coordinated eye movements are significantly impaired when performed after sleep loss and during the biological night, and thus may be contributing to human error and accidents. Because affected individuals are often unaware of their sensorimotor and cognitive deficits, there is a critical need for non‐invasive, objective indicators of mild, yet potentially unsafe, impairment due to disrupted sleep or biological rhythms. Our findings show that a set of eye‐movement measures can be used to provide sensitive and reliable indicators of such mild neural impairments. Abstract: Sleep loss and circadian misalignment have long been known to impair human cognitive and motor performance with significant societal and health consequences. It is well known that human reaction time to a visual cue is impaired following sleep loss and circadian misalignment, but it has remained unclear how more complex visuomotor control behaviour is altered under these conditions. In this study, we measured 14 parameters of the voluntary ocular tracking response of 12 human participants (six females) to systematically examine the effects of sleep loss and circadian misalignment using a constant routine 24‐h acute sleep‐deprivation paradigm. The combination of state‐of‐the‐art oculometric and sleep‐research methodologies allowed us to document, for the first time, large changes in many components of pursuit, saccades and visual motion processing as a function of time awake and circadian phase. Further, we observed a pattern of impairment across our set of oculometric measures that is qualitatively different from that observed previously with other mild neural impairments. We conclude that dynamic vision and visuomotor control exhibit a distinct pattern of impairment linked with time awake and circadian phase. Therefore, a sufficiently broad set of oculometric measures could provide a sensitive and specific behavioural biomarker of acute sleep loss and circadian misalignment. We foresee potential applications of such oculometric biomarkers assisting in the assessment of readiness‐to‐perform higher risk tasks and in the characterization of sub‐clinical neural impairment in the face of a multiplicity of potential risk factors, including disrupted sleep and circadian rhythms. Key points: Inadequate sleep and irregular work schedules have not only adverse consequences for individual health and well‐being, but also enormous economic and safety implications for society as a whole. This study demonstrates that visual motion processing and coordinated eye movements are significantly impaired when performed after sleep loss and during the biological night, and thus may be contributing to human error and accidents. Because affected individuals are often unaware of their sensorimotor and cognitive deficits, there is a critical need for non‐invasive, objective indicators of mild, yet potentially unsafe, impairment due to disrupted sleep or biological rhythms. Our findings show that a set of eye‐movement measures can be used to provide sensitive and reliable indicators of such mild neural impairments.